Pseudomonas aeruginosa PcrV and Psl, the Molecular Targets of Bispecific Antibody MEDI3902, Are Conserved Among Diverse Global Clinical Isolates. (17th July 2018) - Tabor, D E; Oganesyan, V; Keller, A E; Yu, L; McLaughlin, R E; Song, E; Warrener, P; Rosenthal, K; Esser, M; Qi, Y; Ruzin, A; Stover, C K; et al.
Abstract : Whole-genome sequencing of 913 Pseudomonas aeruginosa clinical isolates derived from diverse infections and geographic locations revealed a high prevalence of exopolysaccharide Psl and PcrV, the targets of bispecific monoclonal antibody and clinical candidate MEDI3902. Abstract: Background: Bispecific antibody MEDI3902, targeting the Pseudomonas aeruginosa type 3 secretion system (PcrV) and Psl exopolysaccharide, is currently in phase 2b development for prevention of nosocomial pneumonia in patients undergoing mechanical ventilation. We surveyed a diverse collection of isolates to study MEDI3902 epitope conservation and protective activity. Methods: P. aeruginosa clinical isolates (n = 913) were collected from diverse patients and geographic locations during 2003–2014. We conducted whole-genome sequencing; performed PcrV and Psl expression analyses via immunoblotting and enzyme-linked immunosorbent assay, respectively; performed crystallography to determine the MEDI3902 PcrV epitope, using anti-PcrV Fab and PcrV components (resolved at 2.8 Å); and evaluated MEDI3902 protective activity against select isolates in vitro and in vivo. Results: Intact psl operon and pcrV genes were present in 94% and 99% of isolates, respectively, and 99.9% of isolates contained at least one of the genetic elements. Anti-Psl binding was confirmed in tested isolates harboring a complete Psl operon or lacking nonessential psl genes. We identified 46 PcrV variant sequences, and MEDI3902-PcrV contact residues were preserved. MEDI3902 maintained potent in vivo activity against various strains, including strains expressing only a single target. Conclusions: Psl and PcrV are highly prevalent in global clinical isolates, suggesting MEDI3902 can mediate broad coverage against P. aeruginosa .